Peran Manajemen Mutu Dalam Meningkatkan Kompetensi Guru Pada Era Revolusi Industri 5.0 Di MTSN 1 Bukittinggi - Emeliazola; Zulfani Sesmiarni (Program Studi Pendidikan Agama Islam Fakultas Agama Islam Universitas Nurul Huda, 2024)
Abstrak The purpose of this study was to analyze the role of quality management in improving teacher competence in the era of the Industrial Revolution 5.0. This research uses descriptive qualitative methods to examine the role of quality management in improving teacher competence at MTsN 1 Bukittinggi in the era of the 5.0 Industrial Revolution. The results of this study show that the implementation of quality management practices significantly improved teachers' competencies in professional, pedagogical, personality and social aspects. Key practices include competency-based curriculum development, technology and digital literacy training, and periodic performance evaluation. Through intensive training, teachers are increasingly skilled in using technology and applying digital-based learning methods, such as Learning Management System (LMS) and interactive learning media, which are relevant in the Industrial Revolution 5.0 era. In the pedagogical aspect, teachers are encouraged to develop interactive learning methods such as project-based learning, which increases student motivation and participation. On the personality and social aspects, teachers receive coaching to become more empathetic, responsible and collaborative in the work environment, which strengthens their relationships with students and the community. The implementation of quality management at MTsN 1 Bukittinggi has a positive impact in shaping the competencies of teachers who are adaptive, innovative, and competitive, in accordance with the demands of today's digital education.